Welcome to the Atta world: A framework for understanding the effects of leaf-cutter ants on ecosystem functions - Swanson, Amanda C. (2019)
1. Leaf‐cutter ants are a prominent feature in Neotropical ecosystems, but a comprehensive assessment of their effects on ecosystem functions is lacking. We reviewed the literature and used our own recent findings to identify knowledge gaps and develop a framework to quantify the effects of leaf‐cutter ants on ecosystem processes. 2. Leaf‐cutter ants disturb the soil structure during nest excavation changing soil aeration and temperature. They mix relatively nutrient‐poor soil from deeper layers with the upper organic‐rich layers increasing the heterogeneity of carbon and nutrients within nest soils. 3. Leaf‐cutter ants account for about 25% of all herbivory in Neotropical forest ecosystems, moving 10%-15% of leaves in their foraging range to their nests. Fungal symbionts transform the fresh, nutrient‐rich vegetative material to produce hyphal nodules to feed the ants. Organic material from roots and arbuscular mycorrhizal fungi enhances carbon and nutrient turnover in nest soils and creates biogeochemical hot spots. Breakdown of organic matter, microbial and ant respiration, and nest waste material decomposition result in increased CO2, CH4, and N2O production, but the build‐up of gases and heat within the nest is mitigated by the tunnel network ventilation system. Nest ventilation dynamics are challenging to measure without bias, and improved sensor systems would likely solve this problem. 4. Canopy gaps above leaf‐cutter ant nests change the light, wind and temperature regimes, which affects ecosystem processes. Nests differ in density and size depending on colony age, forest type and disturbance level and change over time resulting in spatial and temporal changes of ecosystem processes. These characteristics remain a challenge to evaluate rapidly and non‐destructively. 5. Addressing the knowledge gaps identified in this synthesis will bring insights into physical and biological processes driving biogeochemical cycles at the nest and ecosystem scale and will improve our understanding of ecosystem biogeochemical heterogeneity and larger scale ecological phenomena.